Soberanas - lugar de mulher é onde ela quiser: o ensino de gênero no ambiente escolar - Simplício, Cláudio César Alves (2022)
The “Sovereigns - A woman's place is wherever she wants” is a pedagogical intervention project that aims to expand dialogue and understanding on issues related to gender relations, with a specific focus on the condition of women and their role in contemporary society, and develop a sequential proposal of activities on gender equality and equity that can be used with students in the school environment during Sociology classes. This sequential proposal of activities on gender equality and equity was used with 1st grade high school students during Sociology and Philosophy classes at the Edson Queiroz State School of Professional Education in Cascavel-CE, in the year of 2020. Due to the current conditions caused by the SARS-CoV-2 virus Pandemic, which causes covid-19, the activities and discussions of the themes planned to be carried out in person, were adapted to the virtual environment, being carried out remotely (synchronous and asynchronous), with the use of digital information and communication technologies. In this work, in addition to a detailed description of the pedagogical intervention, I present the effects of its realization among high school students from audiovisual materials (micro-videos), produced by students, which express their perspectives on gender and sexuality. Such materials showed that the discussions promoted by the intervention went beyond issues related only to women, crossing in an intersectional way to other sociocultural spheres and involving various dimensions of the construction of a gender identity. In addition, the actions developed reinforced that facing these issues can metamorphose the lives of young people and, in this way, indicate new paths of socialization for a youth lacking opportunities.